Dulle Griet ; vanaf (1984) : Dulle Griet-krant. - Dulle Griet (Leuven : Dulle Griet, 1979)
Fonds Suzan Daniel (FSD)
Verantw. uitgeeftster: Els Cottens
Periodiciteit : driemaandelijks
Redactie : Duquesnoystraat 10, 1000 Brussel ; vanaf (1984) Tiensestraat 45, 3000 Leuven
Nederlands
Periodiek
Keywords: vrouwenpers